Personality and Subjective Well-Being among Adolescents on Islamic Boarding School - Sorayati Dwi Utami; Rudi Alfiandi; Fakruddin Fakruddin (GLOBAL HEALTH SCIENCE GROUP, 2025)
Personality and subjective well-being play an important role in a person's life, this is directly related to social interactions, beliefs, and norms that exist around them. This study aims to see the relationship between personality and subjective well-being of adolescents on Islamic boarding school in Rural Aceh. The study applied a cross-sectional study involving 169 from 293 adolescents in an Islamic boarding school in the Aceh Province, Indonesia. Data collection used the Scale of Positive and Negative Experience (SPANE), Satisfaction with Life Scale (SWLS), and Big Five Inventory (BFI). The results of the chi-square test analysis are agreeableness (p-value 0.028), extraversion (p-value 0.036), conscientiousness (p-value 0.033), neurotisisme (p-value 0.019), dan openness to experience (p-value 0.032), its showed there are relationship between personality and subjective well-being of adolescents in Islamic boarding school in Aceh, Indonesia.